The Representation of Peace Values in the Indonesian ELT Textbook Entitled "English for Nusantara" for the Seventh Grade - Lestari, Kartika Puji; Andayani T, Made Adi; Fitriani, Ika (EFL Education Journal, 2024)
Peace values are one of the universal values that are important to be taught in education. ELT textbooks are one of the effective media to transfer them. However, there were still some ELT textbooks published in Indonesia and abroad that had not covered a balanced representation of peace values in them. In addition, the ELT textbooks analyzed mostly still used 13 Curriculum even though currently in Indonesia it had changed to the Emancipated Curriculum. Previous research also mostly examined what types of peace values were represented in ELT textbooks without specifying them. Therefore, this research was conducted to refine previous research and also analyzed what peace values were represented in one of ELT textbooks based on the Emancipated Curriculum by precipitating more crucial types of peace values based on Turnip & Yanto's (2021) explanation. Furthermore, Content Analysis by Ary et al. (2013) was chosen as the analysis method in examining the representation of peace values through visual materials. After that, this research found that peace values were represented equally, namely 4 visual materials in all three types. This was a form of implication that peace values had been well covered in ELT textbooks and could be used as a learning media that could guide students to be peaceful for themselves, society, and the environment.